2004
DOI: 10.1063/1.1643891
|View full text |Cite
|
Sign up to set email alerts
|

Electronic ground states of the V2O4+/0/− species from multireference correlation and density functional studies

Abstract: The molecular and electronic structures of the V2O4+/0/- species are examined by multireference averaged coupled-pair functional (MR-ACPF) and density functional B3LYP calculations. For all three species, new conformers have been found. Shallow potential energy curves imply high mobility of the oxygen atoms in the neutral and anionic species for which antiferromagnetic coupling of the weakly interacting 3dV electrons is found. Good agreement between the MR-ACPF and B3LYP results for the molecular structures an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
57
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 37 publications
5
57
0
2
Order By: Relevance
“…B3LYP was shown previously to describe vanadium-oxide clusters in good agreement with available experimental data as well as quantum chemical methods that explicitly include electron correlation 33. For example, B3LYP reproduced experimental and CCSD(T) results for the dissociation of [VO 2 ] + into [VO] + and 1/2 O 2 ;29c good agreement between multi-reference calculations and B3LYP results has also been found for the molecular structures of V 2 O 4 and the relative energies of its open shell singlet and triplet 34. Thus, this method proved reliable in numerous studies of cationic oxo-cluster ions, containing vanadium and/or phosphorus 9d, 18c, 20a,b, 29c, 3335.…”
Section: Methodssupporting
confidence: 77%
“…B3LYP was shown previously to describe vanadium-oxide clusters in good agreement with available experimental data as well as quantum chemical methods that explicitly include electron correlation 33. For example, B3LYP reproduced experimental and CCSD(T) results for the dissociation of [VO 2 ] + into [VO] + and 1/2 O 2 ;29c good agreement between multi-reference calculations and B3LYP results has also been found for the molecular structures of V 2 O 4 and the relative energies of its open shell singlet and triplet 34. Thus, this method proved reliable in numerous studies of cationic oxo-cluster ions, containing vanadium and/or phosphorus 9d, 18c, 20a,b, 29c, 3335.…”
Section: Methodssupporting
confidence: 77%
“…These B3LYP molecular structures are then used for single point energy calculations at the more elaborate levels (mentioned in the following two sections). In our previous work on bare binuclear vanadium oxide clusters 9 we showed that B3LYP structures do not differ much from those obtained by means of the much more expensive MR-CI calculations. It might be desirable to optimize the molecular structures at MR-CI level, but our computational resources currently do not allow to do so.…”
Section: Density Functional Calculationsmentioning
confidence: 78%
“…Our experience with bare vanadium oxide species 8,9 reveals that DFT calculations provide good molecular structures (geometries), but it must be taken with caution if energetic data is concerned. Therefore we decided to start a series of high level quantum chemical investigations on the gas phase interaction of vanadium oxide cations with small hydrocarbons.…”
Section: Introductionmentioning
confidence: 97%
“…[66] The B3LYP functional has been used previously for a range of vanadium oxide systems, and was shown to give reasonable agreement with available experimental data as well as with higher-level theoretical calculations. [19,20,23,24,27,31,32,[67][68][69][70] Calculations were carried out by using the 6-311 + + G** basis sets for H, C and O, and the SDD effective core potential (ECP) and associated basis sets were used for V. [71] The use of an ECP basis set for V was chosen to allow for direct comparison with the heavier Nb centres. Stationary points were characterized by frequency calculations, and unscaled zero-point energies are included for all species.…”
Section: Methodsmentioning
confidence: 99%